2013
DOI: 10.3109/10717544.2013.860501
|View full text |Cite
|
Sign up to set email alerts
|

Nasal in-situ gels for delivery of rasagiline mesylate: improvement in bioavailability and brain localization

Abstract: Intranasal thermosensitive gel for rasagiline mesylate (RM) was developed for effective treatment of Parkinson's disease. Intranasal gels were prepared by combination of poloxamer 407 and poloxamer 188 (1:1) with mucoadhesive polymers (carbopol 934 P and chitosan). The formulations were evaluated for sol-gel transition temperature, in-vitro drug release and in-vivo mucociliary transit time. Further, optimal intranasal gel formulations were tested for in-vivo pharmacokinetic behavior, nasal toxicity studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Further biological studies in Wistar rats indicated that the intranasal gels were not toxic and non-irritant to the rat nasal mucosa. The RM concentration in the rat brain tissue was significant, indicating an enhanced uptake of RM from the formulation when compared to the drug solution [97]. The administration of the drug intranasally overcomes the extensive first pass metabolism, a mechanism that is responsible for poor drug bioavailability of therapeutics administered orally.…”
Section: In Situ Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Further biological studies in Wistar rats indicated that the intranasal gels were not toxic and non-irritant to the rat nasal mucosa. The RM concentration in the rat brain tissue was significant, indicating an enhanced uptake of RM from the formulation when compared to the drug solution [97]. The administration of the drug intranasally overcomes the extensive first pass metabolism, a mechanism that is responsible for poor drug bioavailability of therapeutics administered orally.…”
Section: In Situ Gelmentioning
confidence: 99%
“…The administration of the drug intranasally overcomes the extensive first pass metabolism, a mechanism that is responsible for poor drug bioavailability of therapeutics administered orally. The extended residence time and intimate contact with nasal epithelium resulting from the mucoadhesive behavior of the gels improved the drug uptake from the nasal cavity [97].…”
Section: In Situ Gelmentioning
confidence: 99%
“…Hematoxylin-Eosin (HE) stained paraffin sections (7 mm) were examined under light microscope. Untreated nasal mucosa was used as a control [33].…”
Section: Histological Studiesmentioning
confidence: 99%
“…The temperature of the medium was maintained at 37±0.5 ° C. Five ml aliquots outgoing for suitable time periods and immediately making the replacement with fresh dissolution medium. The drug content in the withdrawn sample was determined spectrophotometrically by using a UV-Vis spectrophotometer at the selected λ max 285 [14].…”
Section: In Vitro Releasementioning
confidence: 99%